Modelling of a Large Solar PV Facility: England’s Mallard Solar Farm Case Study - Tariq Muneer; Mehreen Saleem Gul; Marzia Alam (Energies, 2022)
With reference to energy generation, the global society has to urgently address three factors that are now critical: sustainability in terms of climate change, security in terms of the war that is currently raging in Europe with consequences that are being felt around the globe and the steep incline of fossil-fuel based energy costs. Around the world, large-scale solar farms are being constructed with tracking systems to improve the efficiency of photovoltaic (PV) modules. This article presents a comparison of energy generation of fixed-slope versus tracking PV modules. The analysis was based on a twenty-year dataset for two locations, namely, Lincoln (England) and Bhavnagar (India), which differ in terms of latitude, sky clarity and ambient temperature. It was demonstrated that a fixed-slope system facing the equator provides a healthy energy receipt that is a high fraction of the energy receipt of a tracking system. Furthermore, analysis was also carried out for a PV facility that will host the largest solar farm in England to conclude that regardless of the solar farm installation location, the use of bifacial PV is beneficial.